2010
DOI: 10.1200/jco.2009.25.2874
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Awareness and Attitudes Toward Decision Aids for Patients With Cancer

Abstract: Approximately one third of physicians treating cancer patients are not aware of what decision aids are, and only 24% are currently using decision aids in clinical practice. Strategies to increase physician awareness about decision aids and to implement these tools into clinical practice are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
(12 reference statements)
0
35
0
Order By: Relevance
“…The belief that PtDA is a relevant source of information for both clinicians and the patients is also supported in other studies [30, 31]. Finally, a lack of knowledge/awareness of PtDAs among health professionals, our sixth most influential factor, is supported by Brace et al [32]. Any implementation strategy for use of PtDAs about DS screening in the clinic needs to specifically consider these six most important factors, a finding consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The belief that PtDA is a relevant source of information for both clinicians and the patients is also supported in other studies [30, 31]. Finally, a lack of knowledge/awareness of PtDAs among health professionals, our sixth most influential factor, is supported by Brace et al [32]. Any implementation strategy for use of PtDAs about DS screening in the clinic needs to specifically consider these six most important factors, a finding consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 57%
“…A highly positive appraisal of three PtDAs was reported by Graham et al in 2007 and to a lesser extent in 2003 [30, 31]. The easy availability of PtDAs as a facilitator has not been clearly reported elsewhere, but their lack of availability has been noted as a disadvantage or barrier, which amounts to the same thing [30, 32]. Graham et al also identified colleagues’ approval as an important influential factor [30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various barriers elicited for their use, physicians mentioned the lack of time and resources. 21 There is a need for an efficient and simple-to-use decision aid that could be integrated in the medical visit without disrupting the consultation.…”
Section: Implications For Practicementioning
confidence: 99%
“…The main barriers to the use of decision aids in practice appear to be a lack of awareness and limited time and resources. 40 Decision-support interventions. In contrast to decision aids, decision-support interventions help people think about the choices they face, describe where and why choice exists, and provide information about options including, where reasonable, the option of taking no action.…”
Section: Patient and Family Engagementmentioning
confidence: 99%